CARDIAC OUTPUT MEASUREMENT IN THE CHILDREN AFTER CARDIAC SURGERY: COMPARISON OF ULTRASOUND MONITORING OF CARDIAC OUTPUT AND ECHOCARDIOGRAPHY - N. P. Leonov; O. V. Strunin; O. V. Poletaeva; V. V. Lomivorotov; A. M. Karaskov (Вестник анестезиологии и реаниматологии, 2018)
The objective: to assess the accuracy of cardiac output measurement by ultrasonic cardiac output monitor (USCOM) versus echocardiography (ECHO) in the children after cardiac surgery.Subjects and methods: A prospective observational trial was conducted (288 patients were assessed for eligibility, and data from 88 patients were analyzed). Cardiac output was measured by USCOM and ECHO.Results. The age of the patients was 305 ± 177 days. Cardiac output measured by USCOM, was 1.310 ± 0.605 [1.182; 1.438] L/min, while the one measured by ECHO made 1.298 ± 0.608 [1.169; 1.427] L/min. ANOVA demonstrated no statistically significant difference (p = 0.89). A significant positive correlation was found between cardiac output rates measured by two methods (r = 0.945 [0.918, 0.964], p < 0.0001). The Bland-Altman plot demonstrated the shift of 0.012 ± 0.200 L/min. and agreement limits from -0.38 to 0.4 L/min. There was no correlation between the shift and median values of cardiac output (r = -0.015 [-0.224, 0.195], p = 0.89).Conclusions. USCOM credibly measures the cardiac output versus the reference method of ECHO. Despite the known limitations, both methods can be used in children after cardiac surgery: USCOM − for screening, ECHO ‒ for deeper examination.